Public Sector Efficiency Applications to Local Governments in Germany - Kalb, Alexander. (Gabler Verlag : Imprint: Gabler Verlag, 2010)
As in the private sector, the principle that resources should not be wasted should also be a key element of decision-makers in the public sector. Alexander Kalb applies advanced and novel econometric as well as linear programming techniques to investigate the sources of potential inefficiencies for local governments in Germany. He uncovers socio-economic, fiscal and political sources of inefficiencies. Finally, he makes recommendations how these inefficiencies in the provision of public goods and services can be reduced in the future.